Dengue hemorrhagic fever and acute hepatitis: a case report - Mourão,Maria Paula Gomes (2004)
Dengue fever is the world's most important viral hemorrhagic fever disease, the most geographically wide-spread of the arthropod-born viruses, and it causes a wide clinical spectrum of disease. We report a case of dengue hemorrhagic fever complicated by acute hepatitis. The initial picture of classical dengue fever was followed by painful liver enlargement, vomiting, hematemesis, epistaxis and diarrhea. Severe liver injury was detected by laboratory investigation, according to a syndromic surveillance protocol, expressed in a self-limiting pattern and the patient had a complete recovery. The serological tests for hepatitis and yellow fever viruses were negative. MAC-ELISA for dengue was positive.